The effect and mechanism of farmland transfer on the multidimensional relative poverty of rural women - Li, Mengding; Zheng, ZhiJia; Zheng, Jiaxi; Yang, Dong; Wang, Tingyu (Frontiers in Environmental Science, 2023)
Over the past 40 years of reform and opening up, China has made significant progress in poverty reduction in rural areas. China's land system is different from other countries in the world because of its special national conditions and the influence of small farmers in large countries.Rural female labor force is the key force to reduce rural poverty and realize rural revitalization. This paper attempts to construct a multidimensional relative poverty measurement index system for rural women, and